DESIGN AND PREPARATION OF PLANT OIL-BASED POLYMERS AND THEIR APPLICATIONS - Ahn, Byung-Jun Kollbe (Kansas State University, 2013)
Renewable materials are desirable for many applications due to the finite fossil resources and environmental issues. Plant oil is one of the most promising renewable feedstocks. Plant oils and functionalized oleo-chemicals including functionalized soybean oils have become attractive sustainable chemicals for industrial applications. Especially, epoxidized oleo-chemicals such as epoxidized soybean oil (ESO) are one of the most well-known readily available inexpensive functionalized plant oils. In this study, novel polymers and nanocomposites for sustainable materials applications were designed and prepared via ring-opening of epoxide in plant oils, and their chemical and physical properties were characterized. The novel transparent elastomers derived from functionalized plant oils have a great potential as flexible electronic and biological applications with their inherent low toxicity. Especially, their rheological properties showed a potential for pressure sensitive adhesives (PSAs). The dominant thermal stability and transparency were obtained via green processing: one pot, single step, fast reactions in moderate conditions, or solvent-free UV curing conditions. These oleo-based elastomers presented excellent end-use properties for PSAs application comparable to commercial PSA tapes. Based on the principal chemical studies, the roles of the each component have been identified: polymer derived from the ring-opening of epoxides as an elastomer, and dihydroxylated triglycerides as a tackifier. Their interaction was also elucidated with an element label analysis. The mechanical and rheological properties of the oleo-polymer as PSAs were able to be improved with a rosin ester tackifier. In addition, biogreases and bio-thermoplastics were developed via the environmentally benign process, which will contribute to further application on the production of new bio-based materials. Further, this study essays a novel acid functionalized iron/iron oxide nanoparticles catalyst with excellent product yields for epoxide ring opening of oleochemicals for a greener synthetic method of biopolyols, and excellent environmental benefits with life cycle assessment of syntheses. Those functionalized iron/iron oxide core shell nanoparticles catalysts has great potential for biomedical engineering process with the highest magnetization of Fe(0) core among all metals.
Keywords: Soybean oil; Polymer; Epoxidized; Adhesive; Agriculture, General (0473); Materials Science (0794)